(untitled) (Journal of Shaheed Suhrawardy Medical College, 2012)
Repairs of incisional (ventral) hernia is one of the commonly performed operation in Bangladesh. This is a prospective study conducted in Shaheed Suhrawardy Hospital, Dhaka and a private Hospital (BDM Hospital) at Dhaka city from June 2001 to 31st May 2004 with a total period of 3 years and with total patients 43. Incisional hernias develop in upto 11% of surgical abdominal wounds with a possible recurrence, following repairs of 44%. There are several methods of repair of incisional hernias, including laparoscopic method of repair which is gaining popularity day by day. But we describe our experience with a combined fascial and prosthetic mesh repair. Of total 43 patients treated, 27 were female & 16 were male. The original operation was gynaecological in 27, bowel related surgery in 15 cases & biliary surgery in 4 patients. The incisions were midline in 31 patients, transverse in 10 patients and paramedian in 2 patients. The hernias were considered subjectively to be large in 21, medium in 16 and small in 6 patients. A parameter was compiled for each patient, noting intraoperative and post postoperative complications , post operative hospital stay and analgesic requirements. Post operative complications included seroma formation in 6 patients. One patient developed wound infection and require removal of the mesh 10 Control infection. Post operative hospital stay ranged from 2 to 17 days. Of total 43 patients 36 were available for follow- up. Seven drops from follow up. Follow up was from 6 months to 36 months. One (2.5%) of these patients complained of persistent lump and one reported persistent pain. Hernia recurrence in one patient (2.5%) , 35 was found to have no recurrence. We advocate these technique because it is applicable to all hernias,most of the mesh is behind the rectus sheath and has two points of fixation, it is relatively pain free allowing early mobilization has a less complication rate and low recurrence rate. DOI: http://dx.doi.org/10.3329/jssmc.v1i2.12158 Journal of Shaheed Suhrawardy Medical College Vol.1, No.2, December 2009 p.6-9